Staphylococcal Scalded Skin Syndrome with Atypical Presentation in nn Infant: A Case Report - Fitri, Laila Kurnia; Subagio, Subagio (Syntax Corporation Indonesia, 2025)
Staphylococcal scalded skin syndrome (SSSS) is a rare, potentially fatal illness caused by Staphylococcus aureus toxins, mainly affecting children under six due to immature immunity and renal function. It presents with fever, rash, blistering, and skin peeling. This report highlights an atypical chronic case with unusual skin presentation. A 7-month-old infant presented with a 3-month history of widespread skin peeling, starting from the face and spreading to the body. No fever or prior drug use was reported. Physical exam showed generalized erythema, desquamation (rough scales), positive Nikolsky sign, and signs of dehydration because of acute diarrhea. Histopathology confirmed Staphylococcal Scalded Skin Syndrome (SSSS). The patient improved after 8 days of hospitalization with supportive and antibiotic therapy. Staphylococcal Scalded Skin Syndrome (SSSS) is caused by epidermolytic exotoxins from certain Staphylococcus aureus strains, leading to skin peeling and large superficial blisters. While often diagnosed clinically, atypical cases may mimic other conditions, making skin biopsy or culture necessary for confirmation.